Is surgery for pineal cysts safe and effective? Short review - Májovský, Martin; Netuka, David; Beneš, Vladimír (Neurosurgical review, 2018)
In this short review, the authors performed a database search and summarize current knowledge of the management of patients with pineal cysts (PCs) and investigate the role of surgical treatment. The scientific literature on the surgical treatment of PCs is sparse and encompasses only case series with little over 200 operated patients combined. All included papers reported favorable results after pineal cyst surgery with improvement of symptoms in most patients. Microsurgical resection of PCs, preferably using the supracerebellar-infratentorial approach, could be considered as a viable treatment option in symptomatic patients. Even patients with non-specific symptoms are reported to improve after surgery. However, evidence offered by this literature review is very limited and therefore our conclusions must be tempered by the restricted set of data. For ethical reasons, a randomized controlled trial is not an acceptable approach, and therefore patient registry could be a useful tool to identify a subset of symptomatic patients that might benefit from pineal cyst resection.
Keywords: Central Nervous System Cysts; výsledek terapie; Humans; Stereotactic biopsy; Patient Selection; Neuroendoscopy; pooperační komplikace; lidé; epifýza mozková; Headache; Hydrocephalus; Postoperative Complications; cysty centrálního nervového systému; Pineal cyst; Brain Neoplasms; Neurosurgery; Treatment Outcome; nádory mozku; Pineal Gland; výběr pacientů